Efek Moderasi Kebijakan Dividen pada Profitabilitas terhadap Nilai Perusahaan Manufaktur - Febriana, Melati; Windhyastiti, Irany; Khouroh, Umu; Ratnaningsih, Christina Sri; Irany Windhyastiti (Business Management Research, 2024)
This research aims to determine the effect of dividend policy as a moderating variable on the influence of profitability on firm value. The population used in this research includes all manufacturing companies listed on the IDX from 2018 to 2022 and the sample was obtained using a purposive sampling method with predetermined criteria and resulted in 9 selected companies from 22 companies. The data analysis technique used is moderated regression analysis (MRA) using the SPSS (Statistical Program for Social Science) appli cation to calculate research data. The results of the research show that: ROA has a negative and significant influence on company value, ROE has a positive and significant influence on company value, Dividend policy has a positive and insignificant influence on value company, Dividend policy is unable to moderate the influence of ROA and ROE on company value